Similarities and differences in polar mesosphere summer echoes observed in the Arctic and Antarctica - R. Latteck; W. Singer; R. J. Morris; W. K. Hocking; D. J. Murphy; D. A. Holdsworth; N. Swarnalingam (Annales Geophysicae, 2008)
Polar Mesosphere Summer Echoes (PMSE) have been observed in the high latitudes of the Northern and Southern Hemisphere for several years using VHF radars located at Andenes/Norway (69° N, 16° E), Resolute Bay/Canada (75° N, 95° W), and Davis/Antarctica (69° S, 78° E). The VHF radars at the three sites were calibrated using the same methods (noise source and delayed transmitting signal) and identical equipment. Volume reflectivity was derived from the calibrated echo power and the characteristics of the seasonal variation of PMSE were estimated at the sites for the years 2004 to 2007. The largest peak volume reflectivity of about 2×10 −9 m −1 was observed at Andenes compared with their counterparts at Davis (~4×10 −11 m −1 ) and Resolute Bay (~6×10 −12 m −1 ). The peak of the PMSE height distribution is 85.6 km at Davis which is about 1 km higher than at Andenes. At Resolute Bay the height distribution peaks at about 85 km but only a few layers were found below 84 km. The mean PMSE occurrence rate is 83% at Andenes, 38% at Davis with larger variability and only 18% at Resolute Bay (in late summer). The duration of the PMSE season varies at Andenes from 104 to 113 days and at Davis from 88 to 93 days. In general the PMSE seasons starts about 5 days later at Davis and ends about 10 days earlier compared to Andenes. In all three seasons the PMSE occurrence suddenly drops to a much lower level at Davis about 32 days after solstice whereas the PMSE season decays smoothly at Andenes. The duration of the PMSE season at Andenes and Davis is highly correlated with the presence of equatorward directed winds, the observed differences in PMSE occurrence are related to the mesospheric temperatures at both sites.